Bruno Arpaia, Javier Cercas (Pordenone, Dedica, 2013, 135 pp., ISBN 9788890700729) (Altre Modernità, 2017)
Bruno Arpaia, Javier Cercas (Pordenone, Dedica, 2013, 135 pp., ISBN 9788890700729)di Gabriele Gelmini